Relationship between the posterior Atrial Wall and the ESOphagus: esophageal position and temperature MEasurement during Atrial Fibrillation ablation. (AWESOME-AF). (19th May 2022) - Teres, C; Soto-Iglesias, DS; Penela, DP; Jauregui, BJ; Ordonez, AO; Chauca, AC; Carreno-Lineros, JMCL; Scherer, CS; Huguet, MH; Ramirez-Paesano, CRP; Camara, OC; Ortiz-Perez, JTOP; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary Vein Isolation (PVI) implies unavoidable ablation lesions on the left atrial posterior wall (LAPW), which is closely related to the esophagus, resulting in several complications. Objective: To evaluate the usefulness of the esophageal isodistance print in avoiding temperature rises caused by radiofrequency (RF) application at the LAPW during paroxysmal AF ablation. Methods: An isodistance map of the atrio-esophageal relationship (esophageal fingerprint) was derived from the preprocedural multidetector computerized tomography MDCT. Patients where randomized on a 1:1 basis in two groups. The PRINT group had a modified PVI line based on the esophageal fingerprint. The CONTROL group underwent standard PVI, and the operator was blinded to the fingerprint (Figure A). Primary endpoint was temperature rise detected by the intraluminal esophageal temperature monitoring probe. The esophageal probe position was verified with the fluoroscopy. Ablation settings were as specified on the Ablate BY-LAW protocol. Results: 60 consecutive patients [42 (70%) men, mean age 60±11 years] referred for paroxysmal AF ablation were randomized. As shown in figure B, a temperature rise (>39, 1ºC) occurred in 5 (16%) patients on the PRINT group Vs. 17 (56%) on the CONTROL group (p<0, 01). Conclusion: The esophageal fingerprint allows for a reliable identification of the esophageal position and its use is superior to standard approach in avoiding esophageal temperature rises. The development of new imaging-derived tools can improve patient safety. Long term follow-up is needed to evaluate for impact of PVI line modification on outcomes in terms of AF recurrence.